Personalized reminiscence therapy M-health application for patients living with dementia: Innovating using open source code repository. - Zhang, Melvyn W. B.; Ho, Roger C.M. (Technology & Health Care, 2017)
Dementia is known to be an illness which brings forth marked disability amongst the elderly individuals. At times, patients living with dementia do also experience non-cognitive symptoms, and these symptoms include that of hallucinations, delusional beliefs as well as emotional liability, sexualized behaviours and aggression. According to the National Institute of Clinical Excellence (NICE) guidelines, non-pharmacological techniques are typically the first-line option prior to the consideration of adjuvant pharmacological options. Reminiscence and music therapy are thus viable options. Lazar et al. [3] previously performed a systematic review with regards to the utilization of technology to delivery reminiscence based therapy to individuals who are living with dementia and has highlighted that technology does have benefits in the delivery of reminiscence therapy. However, to date, there has been a paucity of M-health innovations in this area. In addition, most of the current innovations are not personalized for each of the person living with Dementia. Prior research has highlighted the utility for open source repository in bioinformatics study. The authors hoped to explain how they managed to tap upon and make use of open source repository in the development of a personalized M-health reminiscence therapy innovation for patients living with dementia. The availability of open source code repository has changed the way healthcare professionals and developers develop smartphone applications today. Conventionally, a long iterative process is needed in the development of native application, mainly because of the need for native programming and coding, especially so if the application needs to have interactive features or features that could be personalized. Such repository enables the rapid and cost effective development of application. Moreover, developers are also able to further innovate, as less time is spend in the iterative process.